1990
DOI: 10.2307/3282813
|View full text |Cite
|
Sign up to set email alerts
|

Lernaeocera branchialis: A Potential Pathogen to Cod Ranching

Abstract: A study was carried out to determine the effect of Lernaeocera branchialis on Atlantic cod infected in the laboratory and in the field and also to ascertain its effect on cod-ranching. Sixty-four percent (308) of 481 cod acquired infections in the laboratory and 33% (159) of the infected fish died over a 4-yr period. About 74% of the deaths occurred within 4 mo of the infection. Monthly samples of cod collected adjacent to a cod-ranching operation showed an initial prevalence of 30% that subsequently decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 8 publications
3
23
0
Order By: Relevance
“…For instance, the copepod Salmincola decreases the resistance of its host to environmental stress (Vaughan and Coble 1975;Sutherland and Wittrock 1985) and may decrease the fecundity of female trout (Gall et al 1972). Lernaeocera branchialis, which parasitizes Gadidae living in the Arctoboreal region, has often been associated with host growth reduction (Khan et al 1993) and mortality (Khan and Lacey 1986;Khan et al 1990). Heavy T. polycolpus infestations may have been an additional stress factor contributing to rostrum dace mortality.…”
Section: Pathogenic Effectsmentioning
confidence: 99%
“…For instance, the copepod Salmincola decreases the resistance of its host to environmental stress (Vaughan and Coble 1975;Sutherland and Wittrock 1985) and may decrease the fecundity of female trout (Gall et al 1972). Lernaeocera branchialis, which parasitizes Gadidae living in the Arctoboreal region, has often been associated with host growth reduction (Khan et al 1993) and mortality (Khan and Lacey 1986;Khan et al 1990). Heavy T. polycolpus infestations may have been an additional stress factor contributing to rostrum dace mortality.…”
Section: Pathogenic Effectsmentioning
confidence: 99%
“…Lernaeocera branchialis is recognised as a pathogen that could have major effects on the aquaculture industry (Khan et al 1990, Bricknell et al 2006. With renewed interest in L. branchialis as a result of the expansion of gadoid aquaculture in several North Atlantic countries, this re-description provides important information on its life history, which may form the basis of further research into this potentially devastating pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Bennett & Bennett (2001) found that fish had severe focal haemorrhage due to the penetration of the maxillipeds of the parasite copepod Dissonus manteri into the primary lamella of the leopard coral grouper Plectropomus leopardus, and anaemia was shown to be caused by Lernaeocera branchialis in haddock Melanogrammus aeglefinus (Lester & Roubal 1995), cod Gadus morhua (Khan et al 1990) and hake Merluccius merluccius (Guillaume et al 1985).…”
Section: Discussionmentioning
confidence: 99%